Design of a monitoring system for hospitalized patients based on early warning score - Cano Lengua, Miguel Ángel (2023)
The purpose of this research is to design a Hospitalized Patient Monitoring (MPH) system based on the Modified Early Warning Score (MEWS) system that improves the response time of medical personnel in patient care at a health center in Metropolitan Lima in the year 2022. It is supported by the importance of monitoring the patient's health and the detection of alterations in their vital signs. Therefore, in the development, the MEWS system is used since it allows timely alerting of the patient's worsening, based on the assessment of the measurements of the vital signs that are obtained in the monitoring. On the other hand, the development methodology is based on the Scrum methodological framework, through which a total of 4 Sprints have been carried out, in which the research deliverables are presented. The results indicate that the use case diagram, the entity relationship diagram, the system architecture and the total modeling of the interfaces planned for the investigation are delivered. Likewise, the result of the design validation survey is evaluated using Cronbach's alpha, which gives a reliability coefficient of 0.892, called "Good" within the assessment scale. Thus, it is concluded that the analysis of the system requirements were achieved, the identification of the values of the vital signs measured in the patients in the MEWS system, the establishment of the patient's clinical history, the transfer of information, the referral of the case to the appropriate medical personnel for patient care. In addition, based on the information obtained from a survey, it was possible to record the optimization of the response time of medical personnel in patient care based on the design.